The Virtual World of Social Networking Sites: Adolescent's Use and Experiences. (March 2016) - Pradeep, Pooja; Sriram, Sujata
Social Networking Sites (SNSs) such as Facebook have made inroads in the life of users. The current study used a quantitative approach to explore adolescents' usage of SNS in Mumbai and their perceptions and experiences of the same. The sample consisted of 121 adolescent boys and girls in the age group of 13–18 years. Easily accessible Internet and availability of devices such as smartphones influenced access to SNS. Computer-mediated-communication was the preferred means of communication. Selective self-representation and online social comparison were pertinent themes seen through the study. Gender and age differences were found in the overall usage and experiences of SNS. Parental involvement and monitoring resulted in adolescents engaging in privacy management and helped control risky online behaviour. Overall, adolescents reported more positive experiences with SNS.